TINDAK TUTUR DIREKTIF DAN EKSPRESIF PADA TEKS FILM RUDY HABIBIE (HABIBIE & AINUN 2) KAITANNYA DENGAN SOSIAL DAN BUDAYA - Hayatul Mursida (STAI AL FALAH Banjarbaru, 2020)
This research aims to obtain an objective description of (1) Describing the form and function of the directive and its relation to social and cultural in the text of Rudy Habibie (Habibie & Ainun 2). (2) Describe the form and function of expressive speech and its relation to social and cultural in the text of Rudy Habibie (Habibie & Ainun 2). To achieve that goal, the approach used in this study is to use a qualitative approach and use descriptive methods. This research data is in the form of verbal data, which is a derivative of the characters in the film Rudy Habibie (Habibie & Ainun 2). The data collection techniques used by researchers in this study are similar, note, and descriptive. The form of action directive in Rudy Habibie (Habibie & Ainun 2) includes: (a) the action of the directive of the request in the form of invitations, requests, and invitations marked with the words